Higher education in lower order - Palanithurai, G. (2010)
Higher education has a vast potential to make significant contribution to social and economic development and overall progress of the nation. Being a fundamental mechanism for creation of opportunities for self and societal development, it is essential to ensure that no one is deprived of the opportunity to avail higher education, mainly due to financial constraints. But the ground reality is much different from this imperative because the opportunities for higher education are quite inadequate to our needs. For a variety of reasons large sections of our population do not get desired access to higher education. Most of our universities and Institutions of technical and higher learning woefully fail to meet the standards of quality of higher education. There is an urgent need for determination and maintenance of standards in promotion of higher education and research, and putting in place adequate regulatory mechanism for free pursuit of knowledge, which also ensures access, inclusion and opportunities to all. - Reproduced.
Keywords: Higher education